THE INFLUENCE OF PICTURES AS A MEDIA TO IMPROVE WRITING DESCRIPTION TEXT FOR STUDENTS - Marginingsih Marginingsih; Evi Murti Wardhani; Ginarsiwi Mayangseto (Universitas Duta Bangsa Surakarta, 2022)
This study aims to determine the influence of picture as a medium to improve the skills of writing Descriptive at English Study Program, Faculty of Law and Business Duta Bangsa University Surakarta academic year 2021/2022. Research design is action research. Data collection in this study was carried out by means of conducting observations, individual written tests at the end of learning,. Analytical techniques data using descriptive analysis quantitative. Based on the analysis the results evaluation before and after using picture from cycle I to cycle II can be concluded that the learning of Descriptive Writing by using picture can improve student learning outcomes